Protein digestibility studies in Oreochromis niloticus using chromic oxide indicator. - Lorico, Blesshe V. (Iloilo College of Fisheries, University of the Philippines, 1987)
The indicator method, using 0.5% or 1.0% chromic oxide and the dissection technique of collecting feces were used to evaluate the digestibility of protein by Oreochromisniloticus. High and low protein feedstuffs were evaluated for true and apparent digestibility coefficients inisocaloric diets formulated to contain 30% and 15% protein, respectively. The stomach ans subsequent segments of the intestine were analyzed for their protein and chromic oxide content. Results indicated that animal and plant proteins were highly available to O. niloticus The true digestibility coefficients of tested feedstuffs were corn gluten meal 97% ; soybean 93% ; fish meal 92% ; shrimp meal 87% ; rice bran ; azolla 75% and copra meal 56%. The use of the non-protein diet showed that the anterior intestine was the major site of metabolic nitrogen excretion. The major site for nitrogen absorption in the intestine varied with different feedstuffs. The similar true digestibility coefficients of casein in the 15% and 30% protein diets indicated that true protein digestion was independent of dietary protein level. The effect of fat, carbohydrate and energy levels on protein digestibility was determined in a 2 x 2 factorial experiment using two levels of energy (2,800 kcal/kg and 3,800 kcal/kg) and two levels of fat (6% and 12%), at 30% protein 2%. Increase in fat level from 6% to 12% had no effect on protein digestibility at 2,800 kcal/kg energy level. High level of energy giving low protein : energy (P:E) ratios yielded significantly (P <0.05) lower protein digestibility. The results suggest that fats up to 12% could provide energy to o. niloticus to spare protein as an energy source without negatively affecting protein digestibility and that high energy level resulting to P:E ratios below 83 mg/kcal negatively affect the availability of dietary protein.
Thesis (M. S. Fisheries - Aquaculture) - University of the Philippines in the Visayas, September 1987.
Keywords: Protein; Digestibility; Chromic oxide; indicator; Oreochromis niloticus